POTENSI NANOPARTIKEL PERAK HASIL BIOSINTESIS MENGGUNAKAN EKSTRAK KULIT SENTUL SEBAGAI PENDETEKSI LOGAM MERKURI - Ari Sulistyo Rini; Anggrid Fitrisia; Yolanda Rati (Universitas Riau, 2022)
Silver (Ag) nanoparticles have recently been widely applied due to its high surface plasmon resonance (SPR) properties compared to other metals. In this present work, Ag nanoparticles were prepared through a green synthesis technique that uses sentul peel extracts as a reducing agent. Ag nanoparticles were prepared by reacting AgNO3 and the extract at the volume ratios of 4:1, 3:2, and 1:1. These solutions were heated at 80°C for 30 minutes to form colloidal silver nanoparticles. The optical properties of Ag nanoparticles were characterized using UV-Vis and FTIR spectroscopy. Furthermore, Ag nanoparticles were tested as an indicator of mercury metal detection in term of colorimetric. The UV-Vis absorbance peak of Ag nanoparticles was obtained at wavelengths of 409 nm, 408 nm, and 402 nm. The FTIR spectrum showed the presence of four functional groups, namely, C≡C, C=O, HC≡CH, and O-H. The optimum sample of Ag nanoparticles in the detection of metallic mercury is the 4:1 sample because it shows a significant colour change.